Definition of effectiveness of β-Ni(OH)2 application in the alkaline secondary cells and hybrid supercapacitors - Kovalenko, Vadym; Kotok, Valerii (Eastern-European Journal of Enterprise Technologies, 2017)
Nickel hydroxide is widely used as an active material for alkaline accumulators and hybrid supercapacitors. One of the main parameters of the accumulator and supercapacitor operation is the stability of characteristics. -Ni(OH)2 is the most stable form of nickel hydroxide. To evaluate the effectiveness of using -Ni(OH)2 with high crystallinity in secondary cells and supercapacitors, the method of ultracrystalline-Ni(OH)2 synthesis by slow decomposition of tetraammine nickel hydroxide has been developed. Structural properties of the samples were studied by means of X-ray diffraction and specific surface area was calculated using the BET method from nitrogen desorption experiments. A comparative study of characteristics of ultracrystalline and highly crystalline commercial samples, by means of galvanostatic charge-discharge cycling in the accumulator and supercapacitor regimes was conducted. Low electrochemical effectiveness (coulombic efficiency of 35 %, specific capacity of 101.2 mA·h/g) of ultracrystalline -Ni(OH)2 in accumulator regime was demonstrated. It was discovered, that ultracrystalline -Ni(OH)2, prepared with the decomposition method has high specific characteristics in the supercapacitor regime. At high cycling current densities (40–120 mA/cm2), specific capacities greatly increase, which is explained by the breakdown of hydroxide particle aggregates to smaller ones with an increase of specific surface area. The highest achieved capacities are 120.4 mA·h/g and 276 F/g.